Generatiivisen tekoälyn vastuullinen hyödyntäminen sisällöntuotannossa - Kautto, Emma Oona Vilhelmiina (2024)
Generative artificial intelligence is here to stay, and an increasing number of content producers have adopted various generative artificial intelligence applications in their work. As the name suggests, generative artificial intelligence is an application of artificial intelligence that enables the creation of various types of content, such as text, images, sound, and videos. In terms of content marketing and content production in general, previous research has already identified various use cases for generative artificial intelligence and its concrete benefits. However, the utilization of generative artificial intelligence in content production also involves certain identified risks and responsibility issues. This master's thesis focuses on examining how generative artificial intelligence can be utilized in content production and the identified questions related to the responsible use of generative artificial intelligence based on the experiences of content producers themselves. This study aimed to review previous literature and research material on the subject through a literature review and summarize the key observations and research findings. In addition to the literature review, a qualitative interview study was conducted, involving a total of seven professionals in content production, marketing, and communication. The interviews were conducted as semi-structured interviews. The interview material was analyzed by thematic analysis, and the analysis was deepened using Greimas' actantial model. The results of the study support the observations made in previous research, including the ways generative artificial intelligence is utilized and the identified questions related to the responsible use of generative artificial intelligence. Key benefits identified in this research include speeding up content production, cost efficiency, and assistance with content ideation. The main responsibility issues were related to the accuracy of the content, information security, and copyright issues. The results provide new information about more detailed use cases, the factors supporting and hindering the use of generative artificial intelligence in content production, and the questions related to the responsible use of generative artificial intelligence that content producers have encountered while working with generative artificial intelligence. The results offer new insights and ideas related to the utilization of generative artificial intelligence, considering the key responsibility issues.